2014
DOI: 10.1021/jp509141y
|View full text |Cite
|
Sign up to set email alerts
|

Low-Energy Inverse Photoemission Study on the Electron Affinities of Fullerene Derivatives for Organic Photovoltaic Cells

Abstract: The lowest unoccupied molecular orbital (LUMO) levels of six fullerene derivatives frequently used for organic photovoltaic cells are examined in the solid state. We employed a new experimental technique, low-energy inverse photoemission spectroscopy (LEIPS), which allows us to determine the electron affinities of solid samples within the uncertainties of 0.1 eV. Using the precisely determined electron affinities, the energy difference between the ionization energy of donor and the electron affinity of accepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 62 publications
7
94
0
Order By: Relevance
“…1c)34, and the IP and EA (electron affinity) of PC 71 BM were obtained from literatures35. The IP D of the three pristine films were 4.91, 4.98 and 5.05 eV, respectively, indicating fluorination of the end acceptors increase IP D comparing with those of fluorine atoms attached to the internal part of polymers3637.…”
Section: Resultsmentioning
confidence: 99%
“…1c)34, and the IP and EA (electron affinity) of PC 71 BM were obtained from literatures35. The IP D of the three pristine films were 4.91, 4.98 and 5.05 eV, respectively, indicating fluorination of the end acceptors increase IP D comparing with those of fluorine atoms attached to the internal part of polymers3637.…”
Section: Resultsmentioning
confidence: 99%
“…Despite large differences in chemical and structural properties, both PC 71 BM and P(NDI2OD-T2) have similar E LUMO = ∼−3.8 eV (SI Appendix, Fig. S2) (56), and although absolute performance metrics differ, note that the metrics of all three OPV types consistently track each other, reaching performance maxima at 60 atom % Ga (CBM = −3.93 eV). Although it is likely that factors such as IFL conductivity and mobility play some role in the OPV metric trends observed here, the results in Fig.…”
Section: Significancementioning
confidence: 99%
“…The energy level alignment at different organic/oxide interface structures was next probed using combined UPS and LEIPS techniques. UPS measurements were performed on a-IGO films with 30, 60, and 80 atom % Ga (IGO-30, IGO-60, and IGO-80), stepwise coated with the organic acceptors having different LUMO energies derived from LEIPS as described above [ICBA (∼−3.5 eV), PC 71 BM (∼−3.8 eV) (56), and PDI-CN2 (∼−4.1 eV) (SI Appendix, Fig. S2)].…”
Section: Significancementioning
confidence: 99%
“…We have demonstrated that the electron affinity of organic materials can be determined with the precision comparable to the ionization energy determined by UPS. [27][28][29][30][31][32] Using this technique, we determined the electron affinity of BCP to be 1.9 eV. 30 This value is more than 1 eV smaller than the previously assumed one suggesting that the electron transport through the LUMO level of BCP is unlikely.…”
Section: Introductionmentioning
confidence: 99%